Secondary metabolites from Aquilaria subintegra leaves and their radical scavenging activity - Ibrahim, Mastura; Syed Abdul Azziz, Saripah Salbiah; Wong, Chee Fah; Mohd Hassan, Norazian; Mhd Bakri, Yuhanis; M Abdel Aal, Abu-Baker (Malaysian Institute of Chemistry (Institut Kimia Malaysia), 2024)
The present study reports on the isolation, purification and antioxidant activity evaluation of the dichloromethane extract of Aquilaria subintegra Ding Hou leaves. Four compounds were successfully isolated and purified from the dichloromethane extract using column chromatography. Purification was monitored by thin layer chromatography, and four isolated compounds were identified by spectroscopic analyses such as NMR and mass spectrometry . These compounds were 5-hydroxy-7,4ʹ-dimethoxyflavone, luteolin-7,3ʹ,4ʹ-trimethyl ether, β- sitosterol and friedelin. Their antioxidant activity was determined using 2,2-diphenyl- 1-picrylhydrazyl (DPPH). All compounds exhibited weak antioxidant activity, with inhibition values of less than 30 % at the highest tested concentration (500 μg/mL). To the best of our knowledge, the current study is the first to report on the DPPH radical scavenging activity of isolated secondary metabolites from A. subintegra leaves.